Pengembangan Modul Berbasis Quantum Teaching Pada Mata Pelajaran Matematika Kelas II Sekolah Dasar - Pahlevi, Reza Nazwa; Fatmawati, Risdiana Andika; Nurdiana, Riyanti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aimed to develop a Quantum Teaching-based module motivated by the lack of the use of media by educators, causing monotony and a lack of student response in learning mathematics so that it impacted students’ interest and grades. The use of Quantum Teaching-based modules in learning can help increase students’ interest and enthusiasm. Quantum Teaching-based modules made the students easier to learn independently or need assistance. This research was a developmental research that refered to the Borg and Gall model which used nine stages in the research, (1) research and information collecting, planning, (2) planning, ( 3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, ( 7) operational product revision, (8)operational field testing and (9) final product revision. Based on the research result, the results of media experts found the data with a score 75% with the criteria "Appropriate", from linguists found 69% with the criteria "Appropriate", from material experts found 81% with the criteria "Decent", as well as the results of large-scale field trials with the score of the questionnaire answered by students found 100% with the criteria "Very Practical".